2010
DOI: 10.1177/230949901001800322
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary Cement Embolism during Cement Augmentation of Pedicle Screw Fixation: A Case Report

Abstract: We present a case of pulmonary cement embolism during cement augmentation of pedicle screw fixation for severe degenerative scoliosis. During intra-operative C-arm fluoroscopy, a radio-opaque substance was incidentally noted to pulsate in synchrony with the patient's heartbeat. A diagnosis of pulmonary cement embolism was made. The patient was treated with coumarin for 6 months. He made a good recovery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 6 publications
0
17
0
2
Order By: Relevance
“…However, as in most cases, it was clinically asymptomatic. 1,29,38,39 Due to the low sensitivity of conventional chest radiographs compared with CT scans, a much higher asymptomatic embolism rate must be assumed. 30 Studies of the rate of pulmonary embolism after percutaneous vertebroplasty have reported substantially different rates depending on the detection modality, with radiographs yielding a rate of 6.8%16 and CT yielding a rate of 23%.…”
Section: Symptomatic Leakage Is Rarementioning
confidence: 99%
“…However, as in most cases, it was clinically asymptomatic. 1,29,38,39 Due to the low sensitivity of conventional chest radiographs compared with CT scans, a much higher asymptomatic embolism rate must be assumed. 30 Studies of the rate of pulmonary embolism after percutaneous vertebroplasty have reported substantially different rates depending on the detection modality, with radiographs yielding a rate of 6.8%16 and CT yielding a rate of 23%.…”
Section: Symptomatic Leakage Is Rarementioning
confidence: 99%
“…По некоторым данным [10,15], ее частота варьиру-ет от 2,1 до 26,0 % выполненных опе-ративных вмешательств. В том числе описаны случаи цементной эмболии при выполнении транспедикулярной фиксации с установкой винтов на кост-ный цемент [1]. Чаще всего легочная цементная эмболия асимптоматич-на.…”
Section: Discussionunclassified
“…Calcium phosphate augmentation also increases pull-out strength of pedicle screws; however, in head-to-head studies with PMMA, it has been shown to provide lower pull-out strength [33]. It is important to note that augmentation is not without its own risks, notably the risk of extravasation of cement into the spinal canal, neural foramens, or surrounding vascular structures when the cement or screw is inserted [34,35].…”
Section: Surgical Augmentationmentioning
confidence: 99%